Brain-aging related protein expression and imaging characteristics of mice exposed to chronic hypoxia at high altitude - Cao, Yaxin; Cao, Shundao; Ge, Ri-Li; Bao, Haihua; Mou, Yalin; Ji, Weizhong (Frontiers in Aging Neuroscience, 2023)
Objective To determine changes in protein expression related to brain aging and imaging features in mice after chronic hypoxia exposure at high altitude. Method A total of 24 healthy 4-week-old mice were randomly divided into high altitude hypoxia (HH) and plain control (PC) groups (n = 8 per group). HH mice were transported from Xi’an (450 m above sea level) to Maduo (4,300 m above sea level) while PC mice were raised in Xi’an. After 6 months, 7.0T magnetic resonance imaging (MRI) was performed. All mice completed T2-weighted imaging (T2WI), diffusion tensor imaging (DTI), resting-state functional MRI (rs-fMRI), arterial spin labeling (ASL), and magnetic resonance angiography (MRA) examinations. Next, brain slices were prepared and Nissl staining was used to observe morphological changes in neurons. Ultrastructural changes in neurons were observed by transmission electron microscopy. Expression changes of Caspase-3, klotho, P16, P21, and P53 at the gene and protein levels were detected by real-time PCR (RT-PCR) and Western blot. Results The number of neuronal Nissl bodies in the hippocampus and frontal cortex was significantly decreased in the HH group compared to the PC group. Some hippocampal and frontal cortical neurons were apoptotic, the nuclei were wrinkled, chromatin was aggregated, and most mitochondria were mildly swollen (crista lysis, fracture). Compared with the PC group, the HH group showed elevated expression of caspase-3 mRNA, P16 mRNA, P21 mRNA, and P53 mRNA in the hippocampus and frontal cortex. Expression of Klotho mRNA in the frontal cortex was also significantly decreased. Western blot results showed that caspase-3 protein expression in the hippocampus and frontal cortex of the HH group was increased compared with the PC group. Moreover, there was decreased Klotho protein expression and significantly increased P-P53 protein expression. Compared with the PC group, expression of P16 protein in the frontal cortex of the HH group was increased and the gray matter (GM) volume in the left visceral area, left caudate nucleus, and left piriform cortex was decreased. Furthermore, the amplitude of low frequency fluctuation was decreased in the left posterior nongranular insular lobe, right small cell reticular nucleus, left flocculus, left accessory flocculus, and left primary auditory area, but increased in the GM layer of the left superior colliculus. Regional homogeneity was decreased in the left and right olfactory regions, but increased in the left bed nucleus. After exposure to high altitude, functional connectivity (FC) between the bilateral caudate nucleus and thalamus, corpus callosum, cingulate gyrus, anterior limbic cortex, globus pallidus, and hippocampus was weakened. FC between the right caudate nucleus and hypothalamus and entorhinal cortex was also weakened. The fractional anisotropy value of the left hippocampus was decreased in the HH group. Compared with the PC group, the HH group showed significantly increased inner diameters of the bilateral common carotid artery and left internal carotid artery. The cerebral blood flow values of the bilateral cortex and bilateral hippocampus in the HH group did not change significantly. Conclusion Taken together, our findings show that chronic hypoxia exposure at high altitude may promote neuronal apoptosis and abnormal expression of related proteins, changing the structure and function of brain. These changes may contribute to brain aging.